Ethical review of research into rare genetic disorders. Issue 7460 (29th July 2004) - Parker, M; Ashcroft, R; Wilkie, A O M; Kent, A
Abstract : Although some work on rare diseases is clearly clinical investigation and some clearly research, much activity falls uneasily between the two. Where should we draw the line and how can we ensure research gets appropriate ethical review?